Educational Media: Digital Comics Based on a Contextual Approach on the Topic of the Water Cycle - Suwandinata, I Gede Yuda; Suranata, Kadek (Universitas Pendidikan Ganesha, 2023)
The low understanding of concepts and the lack of utilization of science (IPA) learning media for fifth-grade students in the learning activities are the main issues addressed in this study. The purpose of this research is to develop a contextual-based digital comic educational media on the topic of the water cycle for fifth-grade students in elementary school. The study employs the 4D development model and involves two media experts, two subject matter experts, one teacher, and six fifth-grade students as participants in the product testing phase. Data collection is carried out through questionnaires and analyzed using quantitative and qualitative descriptive analysis techniques. The research findings indicate that the developed digital comic educational media has high validity in terms of content and learning media. The practicality test involving teachers and students shows an achievement level of 94% and 96%, respectively, which indicates excellent criteria. Considering the design, expert validity, and product testing, it can be concluded that the contextual-based digital comic educational media on the water cycle topic for fifth-grade students is considered feasible and can be used as a supporting media in learning activities. It is hoped that the implementation of this media can enrich the science learning process in fifth-grade students and provide a more interactive and enjoyable learning experience. it can be concluded that the contextual-based digital comic educational media on the water cycle topic for fifth-grade students is considered feasible and can be used as a supporting media in learning activities. It is hoped that the implementation of this media can enrich the science learning process in fifth-grade students and provide a more interactive and enjoyable learning experience. it can be concluded that the contextual-based digital comic educational media on the water cycle topic for fifth-grade students is considered feasible and can be used as a supporting media in learning activities. It is hoped that the implementation of this media can enrich the science learning process in fifth-grade students and provide a more interactive and enjoyable learning experience.